Evaluation of Soil Tests for Measuring Potentially Mineralizable Soil N in Southern Idaho Soils. Issue 5 (30th August 2018) - Rogers, C.W.; Schroeder, K.; Rashed, A.; Roberts, T.L.
Abstract : Core Ideas: A reliable rapid soil test method to predict N mineralization is currently unavailable. Chemical and biological soil tests were evaluated against N mineralized by a 7‐d anaerobic incubation. Multiple tests were strongly correlated to the 7‐d anaerobic incubation (e.g., ASN, LOI, and FL_CO2_C). Developing rapid soil tests to predict N availability could improve management strategies for irrigated crops and would assist in sustainable production. No rapid soil test has been evaluated for applicability in irrigated systems in the semiarid western United States. Soils were collected at two sampling depths (0–30 and 30–60 cm) from irrigated fields across southern Idaho representing predominant soil classes, crops, and irrigation management systems; a 0–60 cm depth was calculated. Anaerobic incubations were used to estimate N mineralization (NMIN) in the sampled soils. The tests were positively correlated with NMIN: the amino sugar N (ASN) test was strongly correlated at 0 to 30 cm ( r = 0.73) and 0 to 60 cm ( r = 0.79). The flush of CO2 from soil after capillary rewetting (FL_CO2 _C) was also strongly correlated at the 0‐ to 30‐cm depth ( r = 0.73) and 0‐ to 60‐cm depth ( r = 0.67). The loss on ignition (LOI) test was strongly correlated for the 0‐ to 30‐ ( r = 0.65) and 0‐ to 60‐cm ( r = 0.67) depths. Removal of sites with high soil organic matter resulted in improved r 2 for LOI and ASN but not FL_CO2 _C. The relationship of several tests with NMIN warrants further investigation of their ability to predict crop responses in the region. The ASN test uses a standard 2 M KCl extract, can be automated, and is easily implemented with only minor changes. These results should be expanded to field correlation calibration trials before any test is recommended.